Internet of Things for Monitoring and Controlling Ammonia Gas and Temperature in Chicken Farms - Lifwarda, Lifwarda; Mawandri, Azra; Aulia Rahma, Erin; Ahmad Efendi, Rostam (International Journal of Wireless And Multimedia Communications, 2025)
This research aims to develop a tool to monitor and control temperature and ammonia gas levels in chicken farms. Ammonia gas (NH3) is an indicator of pollution that is harmful to the health of chickens, humans, and the environment. Ideal ammonia levels in cages should not exceed 30 ppm, while the safe threshold for chickens and humans is 25 ppm. High temperatures can increase ammonia levels, thus negatively affecting the health and productivity of broilers. The developed tool uses an MQ135 sensor to detect ammonia gas levels and a DHT22 sensor to measure temperature and humidity. The data obtained will be processed by ESP32 as a microprocessor. The measurement results are displayed on the LCD, and the tool is equipped with a WiFi module to connect it to the internet. A DC fan serves as an automatic control system to keep the temperature and ammonia gas levels within safe limits. Through an application built with MIT App Inventor, users can access real-time temperature data and ammonia gas levels. With this system, it is expected that chicken health and farm productivity can increase, and the risk of pollution due to ammonia gas can be minimized. This research is expected to be a reference for the development of monitoring and control technology in the livestock sector, providing effective solutions for farmers to create a healthier environment for chickens.